Topsy Turvy de Mike Leigh : l’envers du décor ou la norme mise à mal - Isabelle Cases (Cahiers Victoriens et Edouardiens)
In Topsy Turvy, British film-maker Mike Leigh seems to move away from the social cinema he is usually associated with. This film, which is rather unusual in his work, depicts a particular moment in the career of the famous musicians Gilbert and Sullivan, namely the writing and staging of one of their comic operas, The Mikado. Mike Leigh faithfully describes the collaboration between Gilbert and Sullivan, as well as a rigid Victorian society nevertheless characterized by resistance in many ways. The portraits of women and artists are particularly telling in this respect. The film allows Mike Leigh to give his own interpretation of the relationship between norms and transgressions in Victorian times but also to relate his exploration of the period to contemporary themes that are particulary important to him. Topsy Turvy is moreover a reflection on creation in which Mike Leigh subverts a certain number of codes of heritage cinema.